A business model framework for mission-driven organisations - Thackeray, Sean Robin (Rhodes University, Faculty of Commerce, Rhodes Business School)
Non-profit organisations (NPOs) contribute to our society by addressing needs through value-creation activities which are normally not addressed by normal for-profit organisations. These NPOs generate their income through donations, fundraising and market activities such as the sale of products or services. However, in the pursuit of organisational sustainability, these NPOs need to ensure that their income meets their expenditure needs over the long run, to allow continuous value creation and to pursue their mission. An organisation's business model can be visualised through a business model framework (BMF), which have been illustrated to be useful tools for organisations to test new business models, plan and coordinate activities, and to communicate how an organisations business model works to stakeholders. The use of BMFs by NPOs may be useful for similar purposes. However, a key challenge for NPOs and their management is adapting for-profit tools to be more applicable to the NPO environment. Whilst there has been some progress within the literature on adapting these for-profit business model tools to NPOs, this area of research is relatively underrepresented in the literature. The single case study method, exploratory in nature, following a deductive approach with a theoretical framework was used to evaluate the NPO Business model framework for NPOs with multiple income streams (Sanderse, 2014) appropriateness for the Centre for Biological Control (CBC), a mission-driven research organisation located within Rhodes University. The study made use of an interpretivist paradigm through the lens of resource-based theory. The contextual environment of the CBC was similar to other NPOs in that their organisational sustainability was at risk due to uncertainty about the availability of long-term funding. The CBC is actively diversifying their income streams by establishing new partnerships, which increase the capacity and resource base of the organisation to improve its flexibility in meeting current and potential funders' needs. The NPO Business model framework for NPOs with multiple income streams was found to be a suitable BMF to visualise the holistic operations of the CBC. However, the role of governance-related matters being represented in this BMF was found to be lacking. An amended framework including governance as part of the Business model framework for NPOs with multiple income streams was developed. This improved the BMF, by allowing for further contextual insight into the CBCs business model as governance played a major role in the key activities and income-generating strategies they participate in. The role a BMF has in assisting an organisation with resource management activities was also explored. A suitable BMF, which allows for a holistic and explicit display of an organisation's business model, would assist in determining how resources could be better managed or orchestrated to pursue different potential income-generating strategies or improve the efficiency of how resources are used in the current business model. This study contributed to business model theory by further testing the Business model framework for NPOs with multiple income streams as a tool to visualise an NPOs business model and identifying that once the governance block was added, this BMF became more suitable within the CBCs context. A minor contribution to resource based theory was the exploration of the potential roles BMFs play in resource management, which should be further investigated in line with additional research questions proposed.
Keywords: Nonprofit organizations -- South Africa -- Makhanda; Business model; Sustainable development -- South Africa -- Makhanda; Resource-based view; Social responsibility of business -- South Africa -- Makhanda